RESEARCH ON SALMONELLA SPP. AND QUALITY ANALYSIS OF FRESH HOMEMADE MILK MARKETED IN THE MUNICIPALITY OF ANÁPOLIS – GO (CIPEEX, 2025)
This project aims to analyze the microbiological and physicochemical quality of homemade fresh milk marketed in the region of Anápolis - GO, focusing on the detection of Salmonella spp. — a pathogenic microorganism associated with foodborne illnesses. The study is justified by the widespread consumption of raw milk in family and rural settings, often without rigorous sanitary inspection, which poses a public health risk. Several milk samples will be collected throughout one year to perform microbiological and physicochemical analyses, following official methodologies from AOAC, Embrapa, MAPA, and ANVISA. The analyses will include pH, titratable acidity, density, fat content, protein content, cryoscopy, water activity, mesophilic bacteria count, total and thermotolerant coliforms, molds and yeasts, as well as the identification of Salmonella spp. using selective media and confirmatory tests. The results will be compared to the standards established by Normative Instruction No. 76/2018 (MAPA) and Normative Instruction No. 161/2022 (ANVISA). It is expected to find variations in physicochemical parameters and the presence of Salmonella spp. in some samples, highlighting deficiencies in milking and milk preservation practices. The data obtained may support educational initiatives and hygienic-sanitary control strategies, promoting safer artisanal milk production and consumption.
Keywords: Raw milk; microbiology; Salmonella spp